Prevalence and pattern of executive dysfunction in school age children with congenital heart disease. (11th November 2016) - Sanz, Jacqueline H.; Berl, Madison M.; Armour, Anna C.; Wang, Jichuan; Cheng, Yao I.; Donofrio, Mary T.
Abstract: Objective: Executive function, a set of cognitive skills important to social and academic outcomes, is a specific area of cognitive weakness in children with congenital heart disease (CHD). We evaluated the prevalence and profile of executive dysfunction in a heterogeneous sample of school aged children with CHD, examined whether children with executive dysfunction are receiving school services and support, and identified risk factors for executive dysfunction at school age. Design: Ninety‐one school aged patients completed questionnaires, including the Behavior Rating Inventory of Executive Function (BRIEF) and a medical history questionnaire. An age‐ and gender‐ matched control sample was drawn from a normative database. Results: Children with CHD had a higher rate of parent reported executive dysfunction (OR = 4.37, P  < .0001), especially for working memory (OR = 8.22, P  < .0001) and flexibility (OR = 8.05, P  < .0001). Those with executive dysfunction were not more likely to be receiving school services ( P  > .05). Gender, premature birth (≤37 weeks), and CHD with aortic obstruction were predictive of executive dysfunction, especially for behavior regulation skills. Conclusions: School aged children with CHD have an increased prevalence of executive dysfunction, especially problems with working memory and flexibility, and are underserved by the school system. The increased risk for executive dysfunction in those with CHD and prematurity or CHD with aortic obstruction suggests an etiology of delayed brain development in the fetal and neonatal periods, while male gender may increase susceptibility to brain injury. This study highlights the need for regular neurodevelopmental follow up in children with CHD, and a need to better understand mechanisms that contribute to adverse neurodevelopmental outcomes.